2022
DOI: 10.3389/fmed.2022.992565
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights in the role of biomarkers in severe asthma management

Abstract: Contemporary asthma management requires a proactive and individualized approach, combining precision diagnosis and personalized treatment. The introduction of biologic therapies for severe asthma to everyday clinical practice, increases the need for specific patient selection, prediction of outcomes and monitoring of these costly and long-lasting therapies. Several biomarkers have been used in asthma in disease identification, prediction of asthma severity and prognosis, and response to treatment. Novel advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 144 publications
0
4
0
Order By: Relevance
“…It is nowadays widely acknowledged that asthma, although presenting with a limited number of symptoms and signs, is heterogeneous from a pathogenetic standpoint so that different endotypes can be described according to the underlying molecular mechanisms. The most commonly used endotype classifications are based on the dominant cellular type (eosinophilic, neutrophilic, paucigranulocitic or mixed profile) or on the presence of Th2 cytokines (T2-high and T2-low endotype) [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is nowadays widely acknowledged that asthma, although presenting with a limited number of symptoms and signs, is heterogeneous from a pathogenetic standpoint so that different endotypes can be described according to the underlying molecular mechanisms. The most commonly used endotype classifications are based on the dominant cellular type (eosinophilic, neutrophilic, paucigranulocitic or mixed profile) or on the presence of Th2 cytokines (T2-high and T2-low endotype) [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several prior reviews outline the history of biomarkers in asthma precision care [22 ▪ ,25 ▪ ,26]. A recent survey of 412 multinational experts, researchers and clinicians in pediatric asthma, led by the Pediatric Asthma in Real Life (PeARL) think tank, found that precision medicine was a top important unaddressed need, specifically through the use of clinically relevant endotypes, phenotypes, and/or biomarkers (49% of participants) [27].…”
Section: Biomarkers In Asthma Precision Carementioning
confidence: 99%
“…It is easily measured and reproducible. In addition, it has been shown to correlate with risk of exacerbations in patients with SA [ 68 ]. Moreover, eosinophils levels ranging from 150 to 400 cell/µL can also predict the response to treatment with mAbs, targeting the IL-5 pathway.…”
Section: Eosinophils and Bronchial Asthmamentioning
confidence: 99%